THE EFFECT OF SERVICE EXERCISE WITH STAGE DISTANCE ON SERVICE RESULTS IN BALL GAME VOLLEY - Muslimin; Moch. Asmawi; Samsudin (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
This research aims to determine the effect of overhand serves training with a gradual distance on the results of overhand serves in volleyball games on extracurricular students at SMP Negeri 40 Palembang. The sample of this research was 25 students who took volleyball extracurricular activities. Data collection techniques in this research were through structured observation guided by volleyball playing skills tests from the American Association for Health, Physical Education Recreation and Dance (AAHPERD) as the top serves test instrument. Hypothesis testing in this research uses Paired-Samples T Test or t-test with the help of SPSS application (Statistical Product and Service Solutions). The results obtained by tcount (-20,527) < ttable (df /dk 24 = 1,711), which means that there is an influence of overhand serves with a gradual distance to the results of overhand serves in volleyball games on extracurricular students in SMP Negeri 40 Palembang.